Increased Plant Carbon Translocation Linked to Overyielding in Grassland Species Mixtures - De Deyn, Gerlinde B. (Public Library of Science, 2012)
Plant species richness and productivity often show a positive relationship, but the underlying mechanisms are not fully understood, especially at the plant species level. We examined how growing plants in species mixture influences intraspecific rates of short-term carbon (C-) translocation, and determined whether such short-term responses are reflected in biomass yields. We grew monocultures and mixtures of six common C3 grassland plant species in outdoor mesocosms, applied a (13)C-CO(2) pulse in situ to trace assimilated C through plants, into the soil, and back to the atmosphere, and quantified species-specific biomass. Pulse derived (13)C enrichment was highest in the legumes Lotus corniculatus and Trifolium repens, and relocation (i.e. transport from the leaves to other plant parts) of the recently assimilated (13)C was most rapid in T. repens grown in 6-species mixtures. The grass Anthoxanthum odoratum also showed high levels of (13)C enrichment in 6-species mixtures, while (13)C enrichment was low in Lolium perenne, Plantago lanceolata and Achillea millefolium. Rates of C loss through respiration were highest in monocultures of T. repens and relatively low in species mixtures, while the proportion of (13)C in the respired CO(2) was similar in monocultures and mixtures. The grass A. odoratum and legume T. repens were most promoted in 6-species mixtures, and together with L. corniculatus, caused the net biomass increase in 6-species mixtures. These plant species also had highest rates of (13)C-label translocation, and for A. odoratum and T. repens this effect was greatest in plant individuals grown in species mixtures. Our study reveals that short-term plant C translocation can be accelerated in plant individuals of legume and C3 grass species when grown in mixtures, and that this is strongly positively related to overyielding. These results demonstrate a mechanistic coupling between changes in intraspecific plant carbon physiology and increased community level productivity in grassland systems.